Evaluación de la expresión génica de ovarios de Canis lupus familiaris tratados in vitro con Coumestrol - SHEILA IRAIS PEÑA CORONA (2014)
Canine overpopulation is a potential human health risk. Several reproductive control strategies have been used in female dogs such as surgical sterilization, hormone therapy, immunocontraceptionand recently, the use of plant-derived compounds with similar structure to estradiol (phytoestrogens) having estrogenic activity with a direct impact on the reproductive physiology. Up to now, no molecular mechanisms involved in the action of phytoestrogens such as coumestrol are to ovarian level are known. In this study, DNA microarrays were used to identify the expression alterations of potential target genes in order to know the possible mechanisms used by coumestrol. Ovaries from adult female dogs were obtained by surgical dissection and transported to the lab. Cortical 30 mg sections were obtained, embedded in calcium alginate microcapsules with four Coumestrol concentrations (0,1,2,4 and 8 ng/ml) and incubated for a 4 hour period. Total RNA was isolated, quantified and integrity evaluated by alkaline agarose gel electrophoresis. cDNA was labeled with either Alexa555- (Control) or Alexa647-ddUTP (Coumestrol treated) fluorochromes, and used for sequential hybridization of microarrays (M22K_08_31 to 34). We used GenArise to filtrate, transform and normalize the rough data. Z score representing the change in expression level was used as criteria for transcriptional induction or repression. Data having Z values > ±2 were used in MAGNET program for system analysis based on GEO. The Masson trichrome staining of treated fragments and exfoliative vaginal cytology (CVE) from every bitch from where the ovaries were extracted were used to determine the stage in the estral cycle of each female donor dog. Data from follicular diameter and percentage consistent with other studies conducted, and no difference in histoarchitecture after incubation with Coumestrol with any of the concentrations used were found. Determination of estral cycle by vaginal exfoliative citology let us know that 80% of female dogs were at estrous stage ...